Overexpression of and RNA interference with hydroxycinnamoyl-CoA quinate hydroxycinnamoyl transferase affect the chlorogenic acid metabolic pathway and enhance salt tolerance in Taraxacum antungense Kitag. (December 2018) - Liu, Qun; Liu, Yue; Xu, Yachen; Yao, Lixiang; Liu, Zijia; Cheng, Haitao; Ma, Ming; Wu, Jie; Wang, Weiting; Ning, Wei
Graphical abstract: Picture of the T.antungense (A) and T. mongolicum Hand.-Mazz (B). Highlights: CGA biosynthesis regulation and the role of CGA biosynthetic gene were determined in Taraxacum autungense. HQT overexpression and RNA interference lines were generated. TaHQT positively regulated CGA biosynthesis and enhanced salt tolerance. Abstract: Dandelions ( Taraxacum spp.) are wild plants with a long history of use as a functional food and as medicine. Chlorogenic acid (CGA) and caffeic acid (CA) are organic acid components of Taraxacum antungense Kitag. that exhibit antioxidant, anti-inflammatory, and other pharmacological effects. This study aimed to determine the regulatory mechanism of CGA biosynthesis and the role of the CGA biosynthetic gene ( HQT ), encoding hydroxycinnamoyl-CoA quinate hydroxycinnamoyl transferase, in T. antungense . Quantitative real-time polymerase chain reaction revealed significant changes in the tissue distribution of HQT expression in T. antungense transgenic lines overexpressing HQT . CGA but not CA concentrations differed significantly between the wild-type T. antungense and transgenic lines overexpressing HQT. Further, the CGA concentration was significantly higher in the leaves than in the roots. The upregulation of TaHQT elevated the CGA levels by up to 82.49% in the leaves, whereas RNA interference (RNAi) resulted in 51.48% reduction. Comparison of physiological parameters (malondialdehyde, proline, and total chlorophyll concentrations) under salt stress conditions revealed that the overexpression lines were more salt resistant than the wild-type and RNAi lines. These findings indicate that TaHQT positively regulates the CGA biosynthesis and enhances salt tolerance in the overexpression lines.